Pengendalian Persediaan Bahan Baku Impor dengan Menggunakan Metode EOQ Probabilistik pada Perusahaan Cat Industri - Ciswondo Ciswondo; Anastasia Lidya Maukar (JIE Scientific Journal on Research and Application of Industrial System, 2019)
This research was carried out in a manufacturing company producing industrial paints for steel roofing and walling. The level of sales of industrial paint varies and fluctuates depending on product demand from customers. Due to fluctuating demand and forecasting methods for current product demand that is less accurate based only on demand from the previous period, the inventory of imported raw materials has not been optimal. The ARIMA method is used to forecast and then control imported raw material inventories using the probabilistic Economic Order Quantity (EOQ) method to determine the optimal order quantity, safety stock, re-order points and order frequency so as to minimize the total inventory cost. With the probabilistic EOQ method that implements the existence of safety stock will be able to minimize the risk of a shortage of imported raw materials so that the burden of shortage costs can be minimized. The results shows that the proposed method provides a total inventory cost savings of Rp.493,832,731 or obtained a 66% reduce cost compared to the company method